Website Quality and Risk Perception as The Influence of Purchase Intention in E-Commerce Website in Indonesia - Lisnawati, S.Pd., MM, Lisnawati; Hurriyati, Ratih; Al Qorni, Alfi W (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
This study aims to determine the effect of website quality and perceived risk on purchase intention on e-commerce websites.The object of research being the dependent variable is purchase intention and website quality and perceived risk as independent variables. The population in this study is e-commerce Website Visitors in Indonesia. Sampling in this study uses a simple random sampling method (random sampling) using purposive sampling techniques to 198 e-commerce website visitors. The instrument test was conducted with a validity test and a reliability test and the analysis technique used was a structural equation model (SEM). The findings in this study are Website quality has a positive and significant effect on purchase intention, whereas perceived risk has a negative effect on e-commerce website visitors in Indonesia.